Issues and Challenges in Diagnostic Sequencing for Inherited Cardiac Conditions. (6th January 2020) - Walsh, Roddy; Cook, Stuart A
Abstract: BACKGROUND: Inherited cardiac conditions are a relatively common group of Mendelian diseases associated with ill health and death, often in the young. Research into the genetic causes of these conditions has enabled confirmatory and predictive diagnostic sequencing to become an integral part of the clinical management of inherited cardiomyopathies, arrhythmias, aortopathies, and dyslipidemias. CONTENT: Currently, the principle benefit of clinical genetic testing is the cascade screening of family members of patients with a pathogenic variant, enabling targeted follow up of presymptomatic genotype-positive individuals and discharge of genotype-negative individuals to health. For the affected proband, diagnostic sequencing can also be useful in discriminating inherited disease from alternative diagnoses, directing treatment, and for molecular autopsy in cases of sudden unexplained death. Advances in sequencing technology have expanded testing panels for inherited cardiac conditions and driven down costs, further improving the cost-effectiveness of genetic testing. However, this expanded testing requires great rigor in the identification of pathogenic variants, with domain-specific knowledge required for variant interpretation. SUMMARY: Diagnostic sequencing has the potential to become an integral part of the clinical management of patients with inherited cardiac conditions. However, to move beyond just confirmatory and predictive testing, a much greater understanding is needed of the genetic basis of these conditions, the role of the environment, and the underlying disease mechanisms. With this additional information it is likely that genetic testing will increasingly be used for stratified and preventative strategies in the era of genomic medicine.